Partisipasi Perempuan melalui Organisasi Non Pemerintah Fatayat dan Muslimat Nahdlatul Ulama dalam Penanganan Covid-19 - Mayrudin, Yeby Ma'asan; Godjali, Moh. Rizky (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2020)
This article examines the women’s participation through  non-government organizations, namely Fatayat and Muslimat Nahdlatul Ulama (NU) in handling the impact of the Coronovirus Disease 2019 (Covid-19) amidst strong patriarchal culture. The development of patriarchal culture and practices often raises political exclusion from the activities and central roles of women. This was confirmed during the pandemic, the activities and roles of women were intentionally excluded so that they were not widely exposed in the community. Until September 2020 the Covid-19 outbreak tends not to show a positive decline, at this time it is seen that the death rate continues to increase. This becomes very crucial and problematic in the midst of the massive spread of the plague, which requires creative efforts from stakeholders, especially national and regional leadership, which should work together and collaborate with women in dealing with the war with the epidemic. Therefore, the aim of this research is to formulate a puzzle that splits into a unified whole for the phenomenon of activism in the women's organizations movement during the pandemic. Thus, this study focuses on the discussion to dissect the activism and active participation of these women's organizations which are not widely published by various platforms of online and conventional news media. The research method used a qualitative approach with phenomenological methods. The data collection techniques used were interviews and literature studies. This method is useful for dissecting the phenomenon that occurs by observing carefully and examining the social activities of the two Islamic women's organizations in dealing with the impact of the pandemic. The results of this study found that the participation of the two Islamic women's organizations during the pandemic played an important and massive role, but unfortunately it appears to be deliberately excluded so that it is not widely exposed in the community.